Respon Ubi Jalar (Ipomea Batatas L.) Terhadap Pengolahan Tanah Dan Jumlah Ruas Pucuk - F.R, Destyan Fariz; Sulistiyowati, Retno; Zuhroh, Mimik Umi (Agrotechbiz : Jurnal Ilmiah Pertanian, 2022)
Sweet potato (Ipomea batatas L.) is the staple foods for part of Indonesian frequently found at traditional markets with relatively cheap prices. It has potency for substituting rice. This plant adapts well even in less fertile soil conditions, and is resistant to pests and diseases. This study aims to determine the response of sweet potato to the treatment of tillage and the use of shoots as planting material. This research was carried out in the experimental station of IP2TP Muneng Probolinggo, using a divided plot design (RPB) with tillage consisting of 3 levels, namely no-tillage (T0), minimal tillage (T1), and maximum tillage (T2) and shoot segment subplots. The number of shoot segments consists of 3 levels, namely 2 shoot segments (R1), 4 shoot segments (R2), and 6 segments (R3). Results show that 1) maximum tillage treatment (T2) significantly affected plant length, tuber weight, and tuber length, 2) treatment of 4 shoot buds (R2) significantly affected leaf area, wet stover weight, dry stover weight, tuber length and tuber weight, 3) the combination of maximum soil treatment and 4 segments (T2R2) had a very significant effect on tuber weight.Key words: Tillage, Stem Segment, Sweet Potato